DESAIN WADAH TRANSPORTASI TIPE KOMPARTEMEN UNTUK MEMPERPANJANG JARAK TRANSPORTASI DAN MEMPERTAHANKAN KUALITAS BIBIT RUMPUT LAUT Kappaphycus alvarezii PASCA TRANSPORTASI - Lukas, Ade Yulita Hesti; Oedjoe, Marcelien Dj. Ratoe; Tjendanawangi, Agnette; Sunadji, Sunadji; Bunga, Retno Yoanrisco (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
Proper transportation of seaweed seeds is one effort to increase their productivity. Good transportation must be able to guarantee that seaweed seeds arrive at the location in healthy and fresh condition. The research aims to determine the effectiveness of compartment type transportation container design in maintaining the quality of Kappaphycus alvarezii seaweed seeds after transportation for 6 days. This research uses an experimental method with three treatments, namely transportation container design with treatment A with 4 circulation holes, treatment B with 6 circulation holes, and treatment C with 8 circulation holes. Seaweed seedlings were transported for 6 days, with temperature monitoring every 4 hours while ice cubes were replaced every 24 hours. Daily weight loss rates were analyzed using ANOVA while temperature fluctuations in the transportation container were analyzed descriptively. The research results show that using a compartment type transportation container can maintain the temperature in the optimal range, namely 20°C-28°C for ±24 hours and maintain the freshness of seaweed seeds for 6 days of transportation. The compartment type design also makes it easier to replace ice cubes during transportation, thereby extending the transportation distance.